Shanghai bride : her tumultuous life's journey to the West - Tsao, Christina Ching (Hong Kong University Press, 2005)
"This is an autobiography of a woman of unusual strength and determination who grew up in 1930s' Shanghai. Born to a traditional family of China's scholar-official class, she endured incredible suffering as her country was torn apart, first by warlords and later by the invading Japanese Imperial Army. Initially she was given a Western education and, as a teenager, was sought after as a singer of Chinese opera, socializing with tycoons, military officers and statesmen. One of her closest friends was her father's concubine. She witnessed life in the raw in Shanghai as warlordism tore the country apart. When Japan attacked Shanghai, she and her young family took refuge in Hong Kong - until Hong Kong, too, was occupied by the Japanese Imperial Army." "After the war, saddled with an ageing husband who became increasingly paranoid, she took over the responsibility of single-handedly caring for her young children, while teaching herself such skills as shorthand, typing and bookkeeping so as to get, and keep, an office job. Throughout this time, her one ambition in life was to live in the United States, an ambition she ultimately fulfilled after first living in Borneo, then London and Paris. Finally, at the age of 50, she boarded the SS Queen Mary from Southampton, and on that venerable liner's final voyage sailed across the Atlantic. In the United States, she was reunited with all her children, now grown with successful careers of their own."--Jacket.